Ruptured Noncoronary Sinus of Valsalva Aneurysm - Amaury Dagoberto Martínez Hernández; Dayana Pino Jiménez (Medisur)
<!--[if gte mso 9]> 1024x768 <![endif]--> <!--[if gte mso 9]> Normal 0 21 false false false <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->